유,무기계 역삼투 복합막의 제조와 해양심층수의 기능화 특성분석 - 임경빈; Kyung Bin Im; 홍영기; Young Ki Hong (한국섬유공학회지, 2013)
In this study, a microfilter medium was prepared using a melt-blown system and used as a pre-filter in a reverse osmosis (RO) separation system. Asymmetric RO composite membranes, which are inorganic/organic-reverse osmosis (IPO-RO) membranes composed of polysulfone and polyamide with tourmaline nanoparticles, have been designed to develop a new desalination membrane showing high selectivity and permeability. The practical separation performance of IPO-RO composite membranes was investigated for the desalination of seawater, especially for deep ocean water. The separation characteristics of IPO-RO composite membranes were discussed by changing some parameters such as applied pressure and temperature. The permeation flux of the IPO-RO composite membranes was investigated using a module composed of RO plate-frame and spiral wound units. The solute rejection and flux for the IPORO composite membrane were 99.0-99.4% and 7.4-23.3 L/m2 ·h in deep ocean water at 20 oC, respectively. Further, the separation performance of the IPO-RO composite membrane for deep ocean water was very steady-state for a long time. Remarkably, the solution permeated through the IPO-RO composite membrane matched drinking water standards.